Bridging Tradition and Faith: Islamic Da'wah and the Evolution of Malay Marriage Customs in South Sumatra - Yusnita, Eti; Gibtiah, Gibtiah (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
The acculturation of Islam in the marriage customs of the Malay community of South Sumatra reflects a harmonious combination of Islamic values and local customs. Marriage is an important event involving the married individual and the family relationship. This study aims to analyze the acculturation of Islam in the marriage customs of the Malay community of South Sumatra, especially among the Semende tribe. This study uses a qualitative approach with observation, interview, and document analysis methods. The study results show that Islamic values are integrated into the traditional procession of marriage, from pre-marriage to wedding celebrations, creating a balance between local traditions and Islamic law. For example, the marriage custom of "waiting for tubang" in the Semende tribe shows how the roles and responsibilities of the family mandated by Islam are adopted in the customary system. In conclusion, the acculturation of Islam in the marriage customs of the South Sumatran Malay community creates a harmonious and sustainable customary practice, showing that customary law can function as a source of Islamic law as long as it does not contradict the Qur'an and hadith. This research provides important insights for the people of Indonesia, especially the Malay community of South Sumatra, in understanding and appreciating their rich and diverse cultural heritage.